2015
DOI: 10.7841/ksbbj.2015.30.3.125
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Thermotolerant Yeast Kluyveromyces marxianus as a Potential Industrial Workhorse for Biofuel Production

Abstract: Kluyveromyces marxianus is a well-known thermotolerant yeast. Although Saccharomyces cerevisiae is the most commonly used yeast species for ethanol production, the thermotolerant K. marxianus is more suitable for simultaneous saccharification and fermentation (SSF) processes. This is because enzymatic saccharification usually requires a higher temperature than that needed for the optimum growth of S. cerevisiae. In this study, we compared the fermentation patterns of S. cerevisiae and K. marxianus under variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In these processes, thermotolerant yeasts are necessary, because saccharification, generally considered as the overall rate-determining step in SSF or SSCF, is performed by cellulase enzymes with high optimal reaction temperatures (45–55 °C) [14, 17]. A well known thermotolerant yeast, K. marxianus , is a robust strain used for industrial ethanol production [18] and was previously reported to grow and ferment in environments up to 50 °C [19]. K. marxianus also has various benefits over mesophilic yeasts, such as high growth rates, reduced cooling costs, and a broad spectrum of substrates, including xylose [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In these processes, thermotolerant yeasts are necessary, because saccharification, generally considered as the overall rate-determining step in SSF or SSCF, is performed by cellulase enzymes with high optimal reaction temperatures (45–55 °C) [14, 17]. A well known thermotolerant yeast, K. marxianus , is a robust strain used for industrial ethanol production [18] and was previously reported to grow and ferment in environments up to 50 °C [19]. K. marxianus also has various benefits over mesophilic yeasts, such as high growth rates, reduced cooling costs, and a broad spectrum of substrates, including xylose [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the feasibility of conventional process and develop SSF and CBP using lignocellulosic biomass, robust yeast strains with multiple tolerance against high temperature, acidic condition and furan derivatives should be developed. By a series of screening methods, metabolic engineering and evolutionary engineering, mutant or recombinant strains of conventional ( Saccharomyces cerevisiae ), and non‐conventional yeasts ( Zygosaccharomyces bailii, Kluyveromyces marxianus and Hansenula polymorpha ) have been developed to be able to grow over 40–45 °C or in the presence of 24 g L −1 weak acid . In additions, recombinant S. cerevisiae strains overexpressing the HAA1 gene or deficient in the OPI1 gene possessed higher tolerance on acetic acid or lactic acid, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to be able to shorten these processes, and the employed strain should be capable of using various substrates. The strain Kluyveromyces marxianus is currently known to exhibit thermotolerance, making it an industrially robust yeast, because economical production processes, such as simultaneous saccharification and fermentation (SSF) or simultaneous saccharification and co-fermentation (SSCF), prefer high temperatures [5][6][7]. Above all, K. marxianus can utilize various substrates including xylose [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%